A Comparative Approach to Understanding Tissue-Specific Expression of Uncoupling Protein 1 Expression in Adipose Tissue - Shore, Andrew; Emes, Richard D.; Wessely, Frank; Kemp, Paul; Cillo, Clemento; D'Armiento, Maria; Hoggard, Nigel; Lomax, Michael A. (Frontiers in Genetics, 2013)
The thermoregulatory function of brown adipose tissue (BAT) is due to the tissue-specific expression of uncoupling protein 1 (UCP1) which is thought to have evolved in early mammals. We report that a CpG island close to the UCP1 transcription start site is highly conserved in all 29 vertebrates examined apart from the mouse and xenopus. Using methylation sensitive restriction digest and bisulphite mapping we show that the CpG island in both the bovine and human is largely un-methylated and is not related to differences in UCP1 expression between white and brown adipose tissue. Tissue-specific expression of UCP1 has been proposed to be regulated by a conserved 5’ distal enhancer which has been reported to be absent in marsupials. We demonstrate that the enhancer, is also absent in 5 eutherians as well as marsupials, monotremes, amphibians and fish, is present in pigs despite UCP1 having become a pseudogene, and that absence of the enhancer element does not relate to brown adipose tissue-specific UCP1 expression. We identify an additional putative 5’ regulatory unit which is conserved in 14 eutherian species but absent in other eutherians and vertebrates, but again unrelated to UCP1 expression. We conclude that despite clear evidence of conservation of regulatory elements in the UCP1 5’ untranslated region, this does not appear to be related to species or tissues-specific expression of UCP1.